Influence of breathing exercises using method of Body Flex by Greer Childers on to the selected somatic traits of women with overweight and obesity - Maria Radziejowska; Agnieszka Malinowska; Paweł Radziejowski (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Introduction . Overweight and obesity are without any doubts an epidemic of our times, resulting from a change in the living style of the people. Majority of the people reduces the physical activity to the minimum, because of the lack of time they have after the work. That is why we are attacked from time to time by various publications about miraculous methods how to throw away an excessive body weight. In this work is made a close investigation of the method of Greer Childers "Body Flex", which has become very popular among other in the United States and in Russia, because of the simplicity of exercises to be done and the short time necessary to perform them. The essence of exercises of "'Body Flex'' type are the breathing exercises connected with isometric and stretching exercising. The main stress is applied to the lower breathing path with keeping the abdominal muscles tone as well as adding the posture muscles operations, what is as consequence to reduce the body weight, selected body circumferences and to strengthen the muscles exercised. Purpose: The aim of presented work was the comparative assessment of the selected somatic traits of the persons making regularly exercises, at least 5 times a week, using the modified "'Body Flex'' method as well as the assessment of effectiveness of the application of those exercises. Material and methods: The examination has covered a group of 25 persons, which was women in the age range 36 - 63, average age amounted to 58,45 +- 8,92 years, including 16 persons of them constituting the tested group and 9 persons being a control group, which has not made regular exercises. In the tested group was separated: 4 persons' group of women with BMI indicating their obesity, 8 persons' group of women with BMI indicating overweight and 4 persons' group of women with BMI within the limits of the norm. Before and after 1 month's, and for 9 persons - after 2 months' therapy, their BMI index, weight, circumference of waist, hips, circumferences: UI, UII, GI, GII and RI. Results: In the tested group, BMI of the subgroup of women with obesity before the exercises having been applied, amounted to 34.50+-3.48 on the average, after 1 month 34.07+- 3.18 kg/m , after 2 months 31.80+-6.93 kg/m ; BMI of the subgroup of women with overweight before the exercises having been applied, amounted to 27.67+-1.26 kg/m , after 1 month 27.46+-1.16 kg/m , after 2 months 27.11+-3.45 kg/m ; BMI of the subgroup of women within the norm before the exercises having been applied, amounted to 23.26+-1.32 kg/m on the average, after 1 month 23.36+-1.31 kg/m , after 2 months 23.1+-. And in the control group, BMI of the subgroup of women with obesity amounted to 33.37+- (+/-0.79), after 1 month 33.10+- (+/-0.84), for the subgroup of women with overweight amounted to 28.25+- (+/-0.70), after 1 month 28.14+- (+/-0.58). Conclusions: Results obtained both in the tested group and in the control group allow stating that exercises done using the modified method Body Flex have reduced BMI values and the more substantial difference was found in the tested group.